1997
DOI: 10.1093/humrep/12.9.1949
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid substantially increases the retention of motility in cryopreserved/thawed human spermatozoa

Abstract: We have demonstrated previously that hyaluronic acid (HA) improves the velocity and the retention of motility in freshly ejaculated human spermatozoa. In the present work, we examined the effect of HA on cryopreserved/ thawed spermatozoa in four paradigms: (i) effect of HA on sperm motility and velocity in semen; (ii) stabilizing effect of HA after 4 h of incubation when the decline of sperm motility is already detectable; (iii) the duration of improved motility after the separation of spermatozoa from HA by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…In parallel, some studies have found positive effects of this molecule for the refrigerated storage, cryopreservation and incubation of human (Sbracia et al. ) and boar spermatozoa (Yeste et al. ).…”
Section: Discussionmentioning
confidence: 97%
“…In parallel, some studies have found positive effects of this molecule for the refrigerated storage, cryopreservation and incubation of human (Sbracia et al. ) and boar spermatozoa (Yeste et al. ).…”
Section: Discussionmentioning
confidence: 97%
“…It attracts water, thus forming a highly hydrated gel, which in turn promotes expansion of the extracellular surfaces (19). It is interesting that HA also improves motility (20) in fresh and frozen/thawed human sperm (21) and promotes capacitation and acrosome reaction in mammalian sperm (22).…”
mentioning
confidence: 99%
“…Human spermatozoa are not very sensitive to damage caused by rapid initial cooling (cold shock) and they may be more resistant than other cells to cryopreservation damage because of their low water content (50%). Nevertheless, the postthaw motility of human spermatozoa can be ranged between 20 and 50 percent (Sbracia et al 1997). It is believed that the cause of this decrease could be multiple including diminished integrity of the membranes and cryodamage to the membranes of the intracellular compartments, which affects energy metabolism and synthesis.…”
Section: Sperm Banking Protocols and Resultsmentioning
confidence: 99%